Efektivitas Pelayanan Perizinan Berusaha Berbasis Online Single Submission (OSS) Di DPMTPSP Kabupaten Tabanan - Kusumanata, A. A. Sagung Mas Anindya Devi; Supriliyani, Ni Wayan; Prabawati, Ni Putu Anik (CITIZEN CHARTER, 2022)
Online Single Submission (OSS) is here to answer public concerns by providing accelerated business licensing services through Investment Services and One Stop Integrated Services. However, in its implementation there are still many obstacles faced, therefore it is necessary to measure the effectiveness of business licensing services in Tabanan Regency. This research uses a qualitative research type with a descriptive approach. Informant determination technique in this study using purposive sampling method. This study uses the theory of J.P Camble (in Zohriah 2017) which measures the effectiveness of the most common and most prominent public services. Shows that the effectiveness of the Online Single Submission (OSS)-based business licensing service has not been effective.